Role of mineralization inhibitors in the regulation of hard tissue biomineralization: relevance to initial enamel formation and maturation - Margolis, Henry C.; Kwak, Seo-Young; Yamazaki, Hajime (Frontiers in Physiology, 2014)
Vertebrate mineralized tissues, i.e., enamel, dentin, cementum and bone, have unique hierarchical structures and chemical compositions. Although these tissues are similarly comprised of a crystalline calcium apatite mineral phase and a protein component, they differ with respect to crystal size and shape, level and distribution of trace mineral ions, the nature of the proteins present, and their relative proportions of mineral and protein components. Despite apparent differences, mineralized tissues are similarly derived by highly concerted extracellular processes involving matrix proteins, proteases, and mineral ion fluxes that collectively regulate the nucleation, growth and organization of forming mineral crystals. Nature, however, provides multiple ways to control the onset, rate, location, and organization of mineral deposits in developing mineralized tissues. Although our knowledge is quite limited in some of these areas, recent evidence suggests that hard tissue formation is, in part, controlled through the regulation of specific molecules that inhibit the mineralization process. This paper addresses the role of mineralization inhibitors in the regulation of biological mineralization with emphasis on the relevance of current findings to the process of amelogenesis. Mineralization inhibitors can also serve to maintain driving forces for calcium phosphate precipitation and prevent unwanted mineralization. Recent evidence shows that native phosphorylated amelogenins have the capacity to prevent mineralization through the stabilization of an amorphous calcium phosphate precursor phase, as observed in vitro and in developing teeth. Based on present findings, the author proposes that the transformation of initially formed amorphous mineral deposits to enamel crystals is an active process associated with the enzymatic processing of amelogenins. Such processing may serve to control both initial enamel crystal formation and subsequent maturation.